Evil dead 2 [videorecording (Blu-Ray)] - Raimi, Sam; Spiegel, Scott, 1957-; Campbell, Bruce, 1958-; Berry, Sarah, 1960-; Hicks, Dan; DePaiva, Kassie; Domeier, Rick (Lionsgate, 2016)
Ash, the sole survivor of 'The Evil Dead', returns to the same cabin in the woods and again unleashes the forces of the dead. With his girlfriend possessed by the demons and his body parts running amok, Ash is forced to single-handedly battle the legions of the damned as the most lethal-and groovy-hero in horror movie history! Welcome to 'Evil Dead II', director Sam Raimi's infamous sequel to 'The Evil Dead' and outrageous prequel to 'Army of Darkness'!